A single-center randomized controlled study of intraperitoneal hyperthermic chemoperfusion in combination of recombinant human tumor necrosis factor (TNF) in treatment of malignant ascites caused by advanced abdominal cancers. Issue 48 (2nd December 2022) - Wu, Lexia; Zhu, Wanshan; Meng, Jincheng; Wu, Jiaming; Li, Luzhen; Fang, Cantu; Zhang, Huatang
Abstract : Introduction: Malignant peritoneal effusion is a common complication of advanced malignancies, which has a poor prognosis for patients. Hyperthermic intraperitoneal chemotherapy (HIPEC) has been widely used in the treatment of advanced gynecological tumors, especially ovarian cancer (OC). Relative studies have indicated that HIPEC allows for direct exposure of tumor cells to high peritoneal concentrations of cytotoxic drugs without increasing systemic toxicity compared with intravenous treatment. Recombinant human tumor necrosis factor for injection (rmhTNF-NC) is a safely tolerated immunotherapeutic drug that has becoming a mainstay of treatment for malignant effusions. Currently, a prospective study is required to determining the efficacy of rmhTNF-NC plus cisplatin for the treatment of malignant peritoneal effusion for OC. Methods: Design and setting: This is a single-center, open trial will be performed in Zhongshan Affiliated Hospital, Guangzhou University of Chinese Medicine. Participants: Eligible patients will be those with advanced gynecologic cancers and who would be suitable for HIPEC. Intervention and Control: HIPEC with cisplatin and intraperitoneal perfusion with rmhTNF-NC. Co-interventions: Further chemotherapy will be offered to patients as per current practice. Outcomes Pilot study: Patients and clinicians' acceptability of the trial to assist in optimization of recruitment. Primary outcome: One-year overall survival (OS). Secondary outcomes: Progression-free survival (PFS), adverse events. Follow-up: One-year follow-up for OS. Sample size: Twenty patients to demonstrate therapeutic effect of peritoneal effusion caused by OC. Discussion: This trial will determine the effectiveness of HIPEC with cisplatin and intraperitoneal perfusion with rmhTNF-NC for advanced gynecologic cancers, and guide the optimal treatment for these patients.